Estabilidade oxidativa de óleo de soja suplementado com extrato de uva bordô - Carvalho, Marlon Thiago de (2020)
Vegetable oils are widely used in human food, have low oxidative stability and do not resist at factors that cause lipid oxidation, being one of the main causes of deterioration of these products. The by-products (skins and seeds) of the grape processing industry are potential sources of phenolic compounds, which can eliminate free radicals by the antioxidant action, preventing the oxidation process. Thus, this work aims to verify the protection of soybean oil against oxidative degradation, by adding grape seed extract, comparing it with the synthetic antioxidant BHT and evaluating its synergistic effect. In addition, it has the purpose of determining the antioxidant potential by DPPH, ABTS, FRAP and chelating ability, as well as phenolic compounds, flavonoids and trans-resveratrol for the seed extracts. The soybean oil was subjected to thermal stress (60 °C for 12 days) and the oxidative degradation of the oil was monitored through the following analyzes: acidity index, peroxide index, conjugated dienes and trienes, TBARS and oxidative degradation of major fatty acids. The prediction of shelf life was performed by OIT (oxidative induction time), using differential exploratory calorimetry (DSC), and the response to changes in functional groups through ATR-FTIR. The data obtained show that there was no significant difference between the Bordô grape extract, BHT and the combined application of both at their accumulation point of oxidation products (dienes, trienes and peroxides). For acidity analysis, the grape extract caused a significant increase in acidity when compared to pure soy oil and BHT. For TBARS analysis, the grape extract + BHT did not present a good response compared to the individual application of them, with the formation of reactive substances, and the result was equivalent to pure soy oil. Regarding the quantification by chromatography, the grape extract and grape extract + BHT showed the lowest degradation of major fatty acids in the oil, with a significant difference between the other samples. In the analysis by ATR-FTIR, the data obtained for the identified functional groups showed good similarity between oil with BHT and oil with grape extract in bands 2853, 1742 and 1160 cm-1, the other bands showed very small changes with variations lower than 0.5%. The oil with grape extract + BHT did not show a reduction in the bands, showing a very similar response to the oxidized pure soy oil. The DSC analysis showed that the presence of antioxidants is significant in the response obtained, the oil with grape extract + BHT showed higher dependence with temperature and a high value of Ea (activation energy) and A (pre-exponential factor), which resulted in a predicted shelf life at 20 °C of 894 days. The oil with BHT had a shelf life of 44 days and the oil with grape extract of 74 days, both of which had lower dependence with temperature and lower predicted shelf life than pure soy oil (148 days). Thus, the grape seed extract was equivalent to BHT as an antioxidant in soybean oil, showing in the various tests performed an equivalent or higher response, for example in the degradation of fatty acids, in which the grape extract showed the greatest protection. The synergism between the natural and the synthetic antioxidant showed a protective capacity, but with a greater dependence on temperature, which makes it possible to show a better predicted performance at low temperatures.